Social Media Usage on Tourists’ Trip Planning Process Among Youth - Abdul Latif, Samshul Amry; Fouzai@Fauzi, Fatin Shafiqa (Kulliyyah of Languages and Management, 2022)
Purpose: Tourists' reliance on social media has increased in recent years. Tourists favor social media over traditional ones for trip preparation and travel decisions. This study examines social media usage on pre, during, and post-trip planning among domestic visitors. Methods/Design/approach: The results were obtained via self-administered online questionnaires from Malaysian tourists who had previously visited attractions in the state of Pahang. This study quantified social media usage in two areas: trip planning and perceived trust. Findings: The results show that respondents use social media heavily before trips compared to during and after trips, namely Instagram and WhatsApp. The results also suggest that respondents trust and rely on travel information from all the six social media platforms suggested. Implication/Limitations: Future studies may incorporate larger samples from various demographic groups and tourist classifications.